2015
DOI: 10.14198/jhse.2015.102.05
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of motor creativity during primary education

Abstract: Dominguez, D., Diaz Pereira, P.M., & Martinez-Vidal, A. (2015). The Evolution of Motor Creativity during Primary Education. A review. J. Hum. Sport Exerc., 10(2), pp.583-591. A number of researchers have verified the possibility of enhancing motor creativity through specific physical education programmes. Nevertheless,little is known about the developmental pattern or the most critical stages in the acquisition of motor creativity. The broad objective of this study was to determine whether significant changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Hence, further studies are highly recommended to provide further insights. Otherwise, few studies have investigated whether physical fitness or motor performance and creative thinking in childhood may be influenced by age-related stages (Domínguez et al, 2015;Gaul & Issartel, 2016;Runco, 2014). In younger children, the COD and sprint predicted the originality, titles, fluency, and closure, whereas in older, only predicted the closure.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, further studies are highly recommended to provide further insights. Otherwise, few studies have investigated whether physical fitness or motor performance and creative thinking in childhood may be influenced by age-related stages (Domínguez et al, 2015;Gaul & Issartel, 2016;Runco, 2014). In younger children, the COD and sprint predicted the originality, titles, fluency, and closure, whereas in older, only predicted the closure.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to this, other researchers believe that traditional teaching styles can develop creative skills (Oboeuf et al, 2020). Despite such contradictions in recent research, it is suggested to conduct more teaching methods to increase children's creativity (Domínguez et al, 2015).…”
Section: Introductionmentioning
confidence: 91%
“…Researchers acknowledge that creativity is facilitated when divergent thinking mechanisms are activated (Zhang et al, 2020). Their findings highlighted the contribution of movement programs to creative potential development, and the imperative role of a non-judgmental environment, where individuals are free to move spontaneously (Domínguez et al, 2015;Richard et al, 2021). Contrary to this, other researchers believe that traditional teaching styles can develop creative skills (Oboeuf et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Toda essa complexidade foi amplamente ressaltada nas respostas dos participantes para esse estudo, para os quais a criatividade signifi ca essencialmente expressar o novo, o diferente, com perfeição e se adequar ao contexto sem perder de vista a beleza e a essência da performance. Contudo, o que é percebido como criativo só será valorizado se houver o atendimento às exigências dos regulamentos técnicos com perfeição, em que a ginasta consiga expressar uma mensagem por formas diferenciadas, prevalecendo a apresentação das relações harmoniosas entre seu domínio corporal, música, estilo escolhido e aparelho, o que implica em utilizar e desenvolver o que Moraru, Memmert e Kamp 42 , Domínguez, Pereira e Vidal 43 destacam como criatividade motora: capacidade de gerar e apresentar soluções originais e diferentes, a partir da combinação de fl exibilidade e fl uência de ideias associadas por meio do domínio de novas tarefas motoras.…”
Section: Avaliação Da Criatividadeunclassified